Two episodes of biphasic anaphylaxis in a boy allergic to wasp sting. Case report - Izabela Pędzik-Nowak; Ewa Cichocka-Jarosz (Alergologia Polska)
Biphasic anaphylaxis still seems to be an issue that is poorly understood and underestimated in everyday clinical practice. Its frequency ranges from 1% to 15% of anaphylaxis from all causes. Publications addressed to this topic are still infrequent. The case report concerns a 7-year-old boy who experienced two episodes of biphasic anaphylaxis. First of them occurred during anaphylaxis caused by a wasp field sting, the other occurred during the procedure, of an initial dose of allergen immunotherapy with wasp venom. Risk factors for occurrence of biphasic anaphylaxis, as well as the rules of management, are discussed. The described case draws attention to the need for careful interviewing and observation of patients after biphasic anaphylaxis due to the possibility of its recurrence.